Elucidating the glutamatergic processes underlying mismatch negativity deficits in early stage bipolar disorder and schizophrenia: A combined 1H-MRS and EEG study. (June 2019) - Kaur, Manreena; Chitty, Kate M.; Lagopoulos, Jim; Hickie, Ian B.; Duffy, Shantel L.; Hermens, Daniel F.
Abstract: Impairments in mismatch negativity (MMN) in schizophrenia are well-established; these findings have been extended to show impairments at early illness stages and in bipolar disorder. A substantial literature supports MMN as an index of NMDA receptor output, however, few studies have conducted in vivo assessments to elucidate the neurochemical underpinnings of MMN. Sixty young (16–33 years) participants with bipolar disorder (n = 47) or schizophrenia (n = 13) underwent 1 H-MRS and MMN assessment. Glutamate over creatine (Glu/Cr) levels in the anterior cingulate cortex (ACC) and hippocampus were determined and MMN was measured frontally and temporally. Correlational analyses assessed the relationship between MMN amplitudes and Glu/Cr. Any significant relationships were assessed for specificity with a follow up correlation analysis of MMN and n-acetyleaspartate (NAA/Cr). No associations between frontal or temporal MMN and ACC or hippocampal Glu/Cr were noted in the bipolar group. In the schizophrenia group, frontal and right temporal MMN amplitudes corresponded with increased ACC Glu/Cr at the trend-level. Right temporal MMN was similarly significantly associated with NAA/Cr. MMN was not associated with hippocampal Glu/Cr. This work provides in vivo evidence that glutamatergic processes may underlie MMN generation in early stage schizophrenia but not in early stage bipolar disorder suggesting differences in the MMN mechanism in these groups. The negative association between ACC Glu/Cr and MMN is consistent with findings of reduced MMN and increased in vivo glutamatergic neurometabolite levels in early stage schizophrenia. Furthermore, these results indicate that examining in vivo NAA/Cr may have provide additional insights into the MMN mechanism in schizophrenia.